2020
DOI: 10.21203/rs.2.17838/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Lactobacillus plantarum on intestinal integrity and immune responses of egg-laying chickens infected with Clostridium perfringens under the free-range or the specific pathogen free environment

Abstract: Background Necrotic enteritis, which is caused by Clostridium perfringens, has resulted in more than $2 billion losses in the poultry industry every year. Due to the ban of antibiotics in feed industry, alternatives like environment improvement and probiotics have been found to be effective as well. In our study, we aim to explore the protective effect of Lactobacillus plantarum supplementation on CP infected chickens in two environments. Results The results showed that the Clostridium perfringens administrati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Lactobacilli and their metabolites may induce mucus production through regulation of intestinal mucin gene expression (Rosique et al, 2019). Xu et al (2020) demonstrated that dietary supplementation with L. plantarum, in laying hens infected with CP, significantly increased MUC2 gene expression in the ileum. Another study used Bacillus subtilis as a dietary supplement for broiler chickens and demonstrated a significant increase in the expression of intestinal MUC-2 mRNA, whereas supplementation with a multi-strain probiotic resulted in a significant increase in the number of goblet cells, with no detectable alteration of MUC-2 expression (Aliakbarpour et al, 2012).…”
Section: Alteration Of Mucin Production and Competitive Exclusionmentioning
confidence: 94%
“…Lactobacilli and their metabolites may induce mucus production through regulation of intestinal mucin gene expression (Rosique et al, 2019). Xu et al (2020) demonstrated that dietary supplementation with L. plantarum, in laying hens infected with CP, significantly increased MUC2 gene expression in the ileum. Another study used Bacillus subtilis as a dietary supplement for broiler chickens and demonstrated a significant increase in the expression of intestinal MUC-2 mRNA, whereas supplementation with a multi-strain probiotic resulted in a significant increase in the number of goblet cells, with no detectable alteration of MUC-2 expression (Aliakbarpour et al, 2012).…”
Section: Alteration Of Mucin Production and Competitive Exclusionmentioning
confidence: 94%
“…Oxidative Medicine and Cellular Longevity treatment increased the proportion of Lactobacillus and Prevotella and decreased the proportion of Helicobacter and Escherichia_Shigella. Lactobacillus species exerts protective effects on intestinal integrity and immune responses of the animal infected with Clostridium [25]. The improvement of anti-inflammatory status has been reported to be followed by the increase in the abundance of Prevotella [26].…”
mentioning
confidence: 99%
“…Wu et al, 2021). Of particular importance, Lactobacilli have been shown to possess strong antagonistic activity against C. perfringens, inhibit toxin production, reduce proinflammatory cytokines, improve intestinal integrity and immune response, correct microbial dysbiosis, restore performance deficiencies associated with subclinical NE, and protect chickens from clinical NE (Dec et al, 2016;Gong et al, 2020;Guo et al, 2017Guo et al, , 2021Khalique et al, 2019;Kizerwetter-Swida & Binek, 2005, 2016La Cao et al, 2012;La Ragione et al, 2004;Li et al, 2017;Shojadoost et al, 2022;Xu et al, 2020). Lactobacilli are also well known for surviving the harsh environment of the GI tract (Hai et al, 2021;Mandal et al, 2021;Noohi et al, 2021;Vesa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli are key members of the endogenous microbiota of oral, GI, respiratory, and urogenital mucosa and play a key role in regulating local microbiota, restoring barrier function, preventing inflammation associated with GI diseases, improving growth performance, and protecting against infectious diseases (Chen et al, 2021; Han et al, 2021; Hu et al, 2021; Klaenhammer et al, 2002; Li et al, 2018; Manes‐Lazaro et al, 2017; Ouwehand et al, 2002; Siddique et al, 2021; Vineetha et al, 2017; Y. Wang et al, 2021; Wu et al, 2021). Of particular importance, Lactobacilli have been shown to possess strong antagonistic activity against C. perfringens , inhibit toxin production, reduce proinflammatory cytokines, improve intestinal integrity and immune response, correct microbial dysbiosis, restore performance deficiencies associated with subclinical NE, and protect chickens from clinical NE (Dec et al, 2016; Gong et al, 2020; Guo et al, 2017, 2021; Khalique et al, 2019; Kizerwetter‐Swida & Binek, 2005, 2009, 2016; La Cao et al, 2012; La Ragione et al, 2004; Li et al, 2017; Shojadoost et al, 2022; Xu et al, 2020). Lactobacilli are also well known for surviving the harsh environment of the GI tract (Hai et al, 2021; Mandal et al, 2021; Noohi et al, 2021; Vesa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%